(3GdefJXe aj CNHGQ Gdedhc hGdCees - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3eMeO Hf jMji Hf CHj HcQ GdHGHUQi s)
(3ChdgG (B:s
(3jHOC GdehLhO efg HChGNQ MhGOK SfI CQHY hKeGfjf heGFg s
(3BNQgG (B:s
(3HBNQ MhGOK SfI GQHY hKdGKjf hKdGKeGFI s
(3GdfSNI HgG MhGTs
(3jdGMX Cf GdChQGb GdKdGK GdChdi ai ZjQ ehVYgG EPG CfgG ef MhGOK SfI (B311 (3hecGf gPg GdChQGb ai U (B188 (3ef GdfSNIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJGQjNs